Transliteration as a Dimension of Translation - Gayathree, S. (University of Kelaniya, 2017)
Translation is an emerging field. Many challenges are encountered during the process of translation. When a translator finds it difficult to do a translation, she/he can seek for alternatives in order to meet the satisfaction of the target readership. These alternate ways are known as different dimensions of translation. Adaptation, transcreation and transliteration are identified as the major dimensions of translation. This paper analyzes the employment of transliteration in scientific and aesthetic fields. Some words and phrases are difficult to translate at times. Sometimes translators encounter certain challenges in finding the proper equivalents or parallels. In such circumstances, the phonemic sound or the pronunciation of the particular word or phrase is carefully observed and that phonemic sound is transcribed into the script form in the target language, which is known as transliteration. Occasionally, in order to increase clarity or to maintain uniformity transliteration is applied during the process of translation. This study aims at verifying specific instances where transliteration ought to be employed and identifying the techniques and strategies utilized in transliteration in scientific and aesthetic fields in order to meet the satisfaction of the target readership. In this study, descriptive methodology and critical analysis are used to identify the instances of transliteration. Thus, the research study attempts at extending the discourse on transliteration. which is an essential dimension of translation which is necessary to overcome the barriers especially in word-level and to meet the satisfaction of the target readership especially in Scientific and Aesthetic fields. An awareness of this may enrich the performance of translation.
Keywords: Dimensions; Equivalents; Pronunciation; Translation; Transliteration